Peningkatan Pencegahan Fraud melalui Pengedalian Internal dan Good Corporate Governace - Renya Rosari; Jusuf Aboladaka; Poiran Poiran; Pandu Adi Cakranegara; Retno Kusumaningrum (Jurnal Akuntansi dan Pajak, 2023)
Fraud prevention in a company is very important because fraud is certainly detrimental to the company. This study aims to examine and analyze the improvement of fraud prevention through internal control and good corporate governance. This study made 4 state-owned banks as research units and the sample used as respondents was 100 people using purposive random sampling. Data collection techniques using questionnaires distributed to employees who work in one of the state-owned banks. The questionnaire used has been tested for validity and reliability with good criteria. The analysis technique used is multiple linear regression analysis. The results of this study indicate that 1) Internal control has a positive and significant effect on fraud prevention and 2) good corporate governance has a positive and significant effect on fraud prevention. This finding suggests that if the company wants to improve fraud prevention, the company must also improve internal control and good corporate governance.